CaMKII inhibitors: from research tools to therapeutic agents - Pellicena, Patricia; Schulman, Howard (Frontiers in Pharmacology, 2014)
The cardiac field has benefited from the availability of several CaMKII inhibitors serving as research tools to test putative CaMKII pathways associated with cardiovascular physiology and pathophysiology. Successful demonstrations of its critical pathophysiological roles have elevated CaMKII as a key target in heart failure, arrhythmia, and other forms of heart disease. This has caught the attention of the pharmaceutical industry, which is now racing to develop CaMKII inhibitors as safe and effective therapeutic agents. While the first generation of CaMKII inhibitor development is focused on blocking its activity based on ATP binding to its catalytic site, future inhibitors can also target sites affecting its regulation by Ca2+/CaM or translocation to some of its protein substrates. The recent availability of crystal structures of the kinase in the autoinhibited and activated state, and of the dodecameric holoenzyme, provide insights into the mechanism of action of existing inhibitors. It is also accelerating the design and development of better pharmacological inhibitors. This review examines the structure of the kinase and suggests possible sites for its inhibition. It also analyzes the uses and limitations of current research tools. Development of new inhibitors will enable preclinical proof of concept tests and clinical development of successful lead compounds, as well as improved research tools to more accurately examine and extend knowledge of the role of CaMKII in cardiac health and disease.